Entrepreneurship, responsibility of the self and its implications in the public educational context (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2025)
This study examines the implications of entrepreneurship in the educational context, focusing on recent educational and curricular reforms, such as the Brazilian National Common Core Curriculum for Secondary Education (BNCC-EM, acronym in Portuguese) and the National Education Guidelines and Framework Law (LDBEN, acronym in Portuguese), aligning with the perspective of Curriculum Policy Studies. The objective is to analyze how these policies, which promote autonomy and youth protagonism, impact the holistic education of students. Using a qualitative approach based on document analysis and literature review, the study discusses the pros and cons of entrepreneurship as a transversal theme in the curriculum. The results indicate that, although entrepreneurship can foster important skills such as autonomy, creativity, and problem-solving, it risks exacerbating inequalities and promoting an individualistic perspective that overlooks the structural barriers faced by many students. The final considerations highlight the need for an education that balances preparation for the job market with critical and inclusive training, acknowledging the implications of curricular policies in shaping subjectivity and transferring individual responsibilities, often neglecting the social and economic challenges that affect educational equity.Keywords: Student autonomy. Public education. Responsibility of the self.